Widely Distributed Bifunctional Bacterial Cytochrome P450 Enzymes Catalyze both Intramolecular C−C Bond Formation in cyclo‐l‐Tyr‐l‐Tyr and Its Coupling with Nucleobases - Liu, Jing; Harken, Lauritz; Yang, Yiling; Xie, Xiulan; Li, Shu‐Ming (Angewandte Chemie International Edition, 2022)
Tailoring enzymes are important modification biocatalysts in natural product biosynthesis. We report herein six orthologous two‐gene clusters for mycocyclosin and guatyromycine biosynthesis. Expression of the cyclodipeptide synthase genes gymA1–gymA6 in Escherichia coli resulted in the formation of cyclo‐l‐Tyr‐l‐Tyr as the major product. Reconstruction of the biosynthetic pathways in Streptomyces albus and biochemical investigation proved that the cytochrome P450 enzymes GymB1–GymB6 act as both intramolecular oxidases and intermolecular nucleobase transferases. They catalyze not only the oxidative C−C coupling within cyclo‐l‐Tyr‐l‐Tyr, leading to mycocyclosin, but also its connection with guanine and hypoxanthine, and are thus responsible for the formation of tyrosine‐containing guatyromycines, instead of the reported tryptophan‐nucleobase adducts. Phylogenetic data suggest the presence of at least 47 GymB orthologues, indicating the occurrence of a widely distributed enzyme class. Bioinformatic analysis unveiled a widely distributed two‐gene locus (gym) in actinobacteria. Reconstruction of the biosynthetic pathways and biochemical investigation led to the characterization of the cytochrome P450s GymBs as dual‐functional oxidases, which catalyze both intra‐ and intermolecular coupling reactions at different positions of cyclo‐l‐Tyr‐l‐Tyr to generate novel tyrosine‐based alkaloids.